REFLECTING ON SOME NURSING THEORIES BASED ON MELEIS' EVALUATION MODEL - Talita Piccoli; Simony Fabiola Lopes Nunes; Priscilla Cibele Tramontina; Roberta Juliane Tono de Oliveira; Evanguelia Kotzias Atherino dos Santos; Lúcia Narazeth Amante (Universidade Federal do Paraná, 2015)
This article aimed to undertake a comparative reflection on the theories of nursing of Paterson and Zderad, Parse, Watson and Meleis, based on the theory evaluation model and its functional components: focus, client, nursing, health, patient-nursing interaction, environment, problems, and nursing care, as proposed by Meleis. The choice of the academic theorists was explained as these are emerging theories and adhere to the current paradigm, converging towards the holistic view of the human being. After theoretical reflection, it was concluded that, in the theories analyzed, the definition of nursing is clear and explicit, emphasizing its action in the promotion of health and quality of life.